Comparison of Cerebral Blood Volume and Vascular Permeability from Dynamic Susceptibility Contrast-Enhanced Perfusion MR Imaging with Glioma Grade - Law, Meng; Yang, Stanley; Babb, James S.; Knopp, Edmond A.; Golfinos, John G.; Zagzag, David; Johnson, Glyn (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Relative cerebral blood volume (rCBV) and vascular permeability (Ktrans) permit in vivo assessment of glioma microvasculature. We assessed the associations between rCBV and Ktrans derived from dynamic, susceptibility-weighted, contrast-enhanced (DSC) MR imaging and tumor grade and between rCBV and Ktrans.METHODS: Seventy-three patients with primary gliomas underwent conventional and DSC MR imaging. rCBVs were obtained from regions of maximal abnormality for each lesion on rCBV color maps. Ktrans was derived from a pharmacokinetic modeling algorithm. Histopathologic grade was compared with rCBV and Ktrans (Tukey honestly significant difference). Spearman and Pearson correlation factors were determined between rCBV, Ktrans, and tumor grade. The diagnostic utility of rCBV and Ktrans in discriminating grade II or III tumors from grade I tumors was assessed by logistic regression.RESULTS: rCBV was significantly different for all three grades (P ≤ .0005). Ktrans was significantly different between grade I and grade II or III (P = .027) but not between other grades or combinations of grades. Spearman rank and Pearson correlations, respectively, were as follows: rCBV and grade, r = 0.817 and r = 0.771; Ktrans and grade, r = 0.234 and r = 0.277; and rCBV and Ktrans, r = 0.266 and r = 0.163. Only rCBV was significantly predictive of high-grade gliomas (P < .0001).CONCLUSION: rCBV with strongly correlated with tumor grade; the correlation between Ktrans and tumor grade was weaker. rCBV and Ktrans were positively but weakly correlated, suggesting that these parameters demonstrate different tumor characteristics. rCBV is a more significant predictor of high-grade glioma than Ktrans.